1995
DOI: 10.1002/clc.4960180805
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative strategies to assess cardiac risk before noncardiac surgery

Abstract: Summary:The strategies recommended in the preoperative cardiac risk assessment prior to major vascular and nonvascular surgery are reviewed. The role of clinical evaluation, noninvasive stress testing (exercise test, stress myocardial perfusion imaging, stress echocardiography), and Holter monitoring during the preoperative evaluation are outlined and the value of intervention based on the use of each test is discussed. Recommended strategies to evaluate patients based on their clinical risk markers in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Numerous attempts to define a strategy for preoperative cardiac evaluation have been made in the last few years, reflecting the lack of consensus among the different teams. 4,12,19,[38][39][40][41][42][43] This diversity may also reflect the challenge to physicians of trying to implement guidelines. 44 Several authors have shown that no single implementation strategy is appropriate; each strategy is influenced by the person using the guidelines, by the incentive system, and by the guidelines' content.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous attempts to define a strategy for preoperative cardiac evaluation have been made in the last few years, reflecting the lack of consensus among the different teams. 4,12,19,[38][39][40][41][42][43] This diversity may also reflect the challenge to physicians of trying to implement guidelines. 44 Several authors have shown that no single implementation strategy is appropriate; each strategy is influenced by the person using the guidelines, by the incentive system, and by the guidelines' content.…”
Section: Discussionmentioning
confidence: 99%
“…These include diabetic patients needing renal transplantation or major non-cardiac vascular surgery in whom coronary revascularisation may reduce the procedural risk. [14][15][16] Anti-anginal drugs…”
Section: Diagnosis Of Angina In Diabetesmentioning
confidence: 99%